The Implications of Sufism Akhlaqi to Strengthen The Noble Morals of Indonesian Students - Fahrudin, Fahrudin; Islamy, Mohammad Rindu Fajar; Faqihuddin, Achmad; Parhan, Muhamad; Kamaludin, Kamaludin (el Harakah: Jurnal Budaya Islam, 2024)
The world of education today faces a variety of complex and diverse challenges. One significant challenge is the shift towards the industrial era 4.0, which potentially negatively impacts student morals. This study explores the concept of Sufism akhlaqi as proposed by experts and its implications for teaching Islamic Religious Education (IRE) at a university in Indonesia, aiming to strengthen students' noble morals. The research employs a qualitative approach, utilizing a descriptive-analytical method through literature review. The findings of this study indicate that: (1) Sufism akhlaqi emphasizes the purification of the soul to strengthen students' noble character; (2) The implications of the Sufism akhlaqi concept for IRE teaching support the instructional objectives of fostering faith and piety in students, while also focusing on promoting noble morals. IRE learning materials should integrate the values of Sufism akhlaqi in each relevant subject, and lecturers must serve as role models of noble morals. Dunia pendidikan saat ini menghadapi berbagai tantangan yang kompleks dan beragam. Salah satu tantangan yang cukup besar adalah peralihan menuju era industri 4.0 yang berpotensi memberikan dampak negatif terhadap moral mahasiswa. Penelitian ini mendalami konsep tasawuf akhlaqi yang dikemukakan oleh para ahli dan implikasinya dalam pengajaran Pendidikan Agama Islam (IRE) di salah satu universitas di Indonesia, yang bertujuan untuk memantapkan akhlak mulia mahasiswa. Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan metode deskriptif-analitis melalui tinjauan pustaka. Temuan penelitian ini menunjukkan bahwa: (1) tasawuf akhlaqi menekankan pada penyucian jiwa untuk memperkuat akhlak mulia peserta didik; (2) Implikasi konsep tasawuf akhlaqi terhadap pengajaran IRE mendukung tujuan pembelajaran untuk menumbuhkan keimanan dan ketakwaan pada peserta didik, sekaligus fokus pada peningkatan akhlak mulia. Materi pembelajaran IRE hendaknya mengintegrasikan nilai-nilai tasawuf akhlaqi pada setiap mata pelajaran yang relevan, dan dosen harus menjadi teladan akhlak mulia.